Plasmid-mediated resistance to cephalosporins and fluoroquinolones in various Escherichia coli sequence types isolated from rooks wintering in Europe - Jamborova, Ivana; Dolejska, Monika; Vojtech, Jiri; Guenther, Sebastian; Uricariu, Raluca; Drozdowska, Joanna; Papousek, Ivo; Pasekova, Katerina; Meissner, Wlodzimierz; Hordowski, Jozef; Cizek, Alois; Literak, Ivan (Applied and environmental microbiology, 2015)
Extended-spectrum-beta-lactamase (ESBL)-producing, AmpC beta-lactamase-producing, and plasmid-mediated quinolone resistance (PMQR) gene-positive strains of Escherichia coli were investigated in wintering rooks (Corvus frugilegus) from eight European countries. Fecal samples (n = 1,073) from rooks wintering in the Czech Republic, France, Germany, Italy, Poland, Serbia, Spain, and Switzerland were examined. Resistant isolates obtained from selective cultivation were screened for ESBL, AmpC, and PMQR genes by PCR and sequencing. Pulsed-field gel electrophoresis and multilocus sequence typing were performed to reveal their clonal relatedness. In total, from the 1,073 samples, 152 (14%) cefotaxime-resistant E. coli isolates and 355 (33%) E. coli isolates with reduced susceptibility to ciprofloxacin were found. Eighty-two (54%) of these cefotaxime-resistant E. coli isolates carried the following ESBL genes: blaCTX-M-1 (n = 39 isolates), blaCTX-M-15 (n = 25), blaCTX-M-24 (n = 4), blaTEM-52 (n = 4), blaCTX-M-14 (n = 2), blaCTX-M-55 (n = 2), blaSHV-12 (n = 2), blaCTX-M-8 (n = 1), blaCTX-M-25 (n = 1), blaCTX-M-28 (n = 1), and an unspecified gene (n = 1). Forty-seven (31%) cefotaxime-resistant E. coli isolates carried the blaCMY-2 AmpC beta-lactamase gene. Sixty-two (17%) of the E. coli isolates with reduced susceptibility to ciprofloxacin were positive for the PMQR genes qnrS1 (n = 54), qnrB19 (n = 4), qnrS1 and qnrB19 (n = 2), qnrS2 (n = 1), and aac(6')-Ib-cr (n = 1). Eleven isolates from the Czech Republic (n = 8) and Serbia (n = 3) were identified to be CTX-M-15-producing E. coli clone B2-O25b-ST131 isolates. Ninety-one different sequence types (STs) among 191 ESBL-producing, AmpC-producing, and PMQR gene-positive E. coli isolates were determined, with ST58 (n = 15), ST10 (n = 14), and ST131 (n = 12) predominating. The widespread occurrence of highly diverse ESBL- and AmpC-producing and PMQR gene-positive E. coli isolates, including the clinically important multiresistant ST69, ST95, ST117, ST131, and ST405 clones, was demonstrated in rooks wintering in various European countries.
Keywords: Crows; pulzní gelová elektroforéza; Multilocus Sequence Typing; Genes, Bacterial; Fluoroquinolones; Escherichia coli; Electrophoresis, Gel, Pulsed-Field; Genotype; antibakteriální látky; plazmidy; vrány; zvířata; Europe; Cephalosporins; Anti-Bacterial Agents; Drug Resistance, Bacterial; multilokusová sekvenční typizace; bakteriální geny; polymerázová řetězová reakce; Polymerase Chain Reaction; genotyp; bakteriální léková rezistence; fluorochinolony; Animals; Plasmids; cefalosporiny; Evropa